MIKROHIDRO UNTUK SOLUSI DAERAH TERPENCIL - Sunardi, Sunardi (Sekolah Tinggi Teknologi Adisutjipto, 2017)
Electricity is one of the most elements needed in the life for any activities and productivities. In the other side, no electricity is the classically problem occurred for the any remote areas caused by no electricity supply by the agent of government. We are required to overcome the problem based on laverage of the existing resource, such as water, geothermal, wind, solar, etc. A small system use the waterflow in order to generate an electrical system known as microhydro has been developed for remote area in District Wonosobo Central Java. There are a waterways or water channel as a result of the dam of Galuh River. Flow of clean water condition has a constant throughout the year. Drains and location of research has a height difference of 6 m therefore has potential enough power to drive a turbine through an 25 cm diameter of a pipe used for the water input. The microhydro system has been developed with maximal capacity of 3000 kW. Electricity produced has been used for street lighting and any small enterprises, i.e. fish pond, chicken farm, and mushroom cultivation. This area was previously not affordable, now by this electricity become bright and productive.